"The Line Must Be Drawn Somewhere": The Rise of Legal Status Restrictions in State Welfare Policy in the 1970s. Issue 2 (October 2019) - Fox, Cybelle
Abstract : In 1971, Governor Ronald Reagan signed into law a measure barring unauthorized immigrants from public assistance. The following year, New York State legislators passed a bill to do the same, although that bill was vetoed by Governor Nelson Rockefeller. This article examines these cases to better understand why states that had long provided welfare to unauthorized immigrants each sought to bar them from public assistance. Common explanations for the curtailment of immigrant social rights often center on partisan politics, popular nativism, demographic context, or issue entrepreneurs. But these studies often wrongly assume that efforts to limit immigrant social rights began in the 1990s. Therefore, they miss how such efforts first emerged in the 1970s, and how these restrictive measures were initially closely bound up in broader debates over race and welfare that followed in the wake of the War on Poverty and the civil rights movement. Where scholars often argue that immigration undermines support for welfare, I show how the turn against welfare helped to undermine immigrant social rights. I also show how differing interpretations of the scope and reach of Supreme Court decisions traditionally seen as victories for welfare and immigrant rights help explain initial variation in policy outcomes in each state.